Polyunsaturated fatty acids from eel extract attenuate gastritis and hepatotoxic by Indomethacin-induced in rats - Sasongko, Heru; Brilian, Aulia Yulfa; Octafiani, Hardiana Fega; Alfasina, Nabila Rachma; Cahyadi, Muhammad; Sutarno (Penerbit Universiti Kebangsaan Malaysia, 2023)
Nonsteroidal anti-inflammatory drugs (NSAIDs) potentially induce hepatotoxicity and ulcerative lesions in the stomach. Several studies have been conducted on the benefits of natural resources to overcome the problem of drug side effects. However, the use of fishery resources, such as the eel (Anguilla bicolor), for medicine has not been widely studied. Eels are rich in omega-3 polyunsaturated fatty acids with antioxidant and anti-inflammatory effects. Therefore, this study aims to determine the gastroprotective and hepatoprotective effects of polyunsaturated fatty acids extracted from eel (FaE). The experimental models were 42 male rats divided into seven groups. The experiment was performed for 14 days by orally administering FaE samples. On the 15th day, the rats were orally induced with indomethacin (48 mg/kg). After 8 h of induction, they were euthanized using ketamine and xylazine. Furthermore, blood samples were collected from the animals to measure the levels of aspartate aminotransferase and alanine aminotransferase. Malondialdehyde (MDA) and glutathione (GSH) levels were measured, while the histology of the liver and stomach were examined. The results showed that the administration of FaE from a dose of 1000 mg/ kg significantly attenuated the liver and stomach damage caused by indomethacin. The influence of oxidative stress inhibition on damage is characterized by inhibition of the increase in MDA and a decrease in GSH. This research shows that FaE has the potential to inhibit liver and gastric damage due to the use of NSAIDs. However, further investigation needs to be conducted on other specific parameters of the inflammatory mechanism.